FUNGAL ALLERGY: AEROBIOLOGICAL ASPECTS IN SAMARA - K. S. Mazokha; M. V. Manzhos; N. N. Zhukova; L. R. Khabibulina; N. V. Vlasova; L. M. Kavelenova; A. S. Zatsepin; A. A. Krasnova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
Objective: to analyze dynamics of sporulation of mold fungi in order to predict the risks of exacerbation of allergic diseases in Samara.Materials and methods. We evaluated the concentration of fungal spores between April 1st and September 30th in 2016–2019 in the air. Mold spores were captured using an impactor trap on slides covered with a mixture of vaseline and wax with subsequent counting of spore number and their identification.Results. The mean vegetative period of mold fungi in Samara city was 164 days. We have identified spores of Cladosporium and Alternaria, which accounted for 34.4 % of the total number of spores in the atmospheric air of Samara. Cladosporium spores were detected during the entire observation period; their proportion was 15.3% from the total number of fungal spores, their maximum concentrations were within the normal limits and did not exceed 960 spores/m3. The proportion of Alternaria spores was 19.1%. In some periods, concentrations of Alternaria spores exceeded threshold values: the concentration between 10 and 100 spores/m3 was observed 4 to 31 days per months; the concentration above 100 spores/m3 was observed 2 to 25 days per month. The highest total monthly concentration of Alternaria spores was detected in July–September, during the period of sagebrush and ragweed pollination, which can potentially hamper the diagnosis and treatment of patients who have exacerbations of their allergic diseases in this period.Conclusion. We have identified the main taxa of mold fungi, analyzed their regional specificity and assessed the risk of allergic diseases in individuals sensitized to Alternaria and Cladosporium species. Our findings will help to optimize the diagnosis, treatment, and prevention of allergic diseases in the region.